Temporal heterogeneity in primary and secondary metabolic products of medicinal plants of Sitamata Wildlife Sanctuary in Rajasthan, India - Soni, Arti; Kasera, Pawan Kumar (Bangladesh Journal of Botany, 2020)
Phyto-chemical investigation in three tuberous medicinal plants, viz., Arisaema tortuosum (Wall.) Schott, Chlorophytum tuberosum (Roxb.) Baker and Curculigo orchioides Gaertn., growing in Sitamata Wildlife Sanctuary of Rajasthan were conducted for both primary and secondary metabolites. Experiment was carried out during June to October to find out monthly variation in accumulation of both primary (total contents of sugars, crude protein and phosphorus) and secondary metabolites (total contents of alkaloids and phenols) in tubers of these three species. In A. tortuosum (Wall.) Schott, crude protein and total alkaloids were found maximum during September, whereas phosphorus and total phenols during July. In C. tuberosum (Roxb.) Baker and C. orchioides Gaertn. maximum values of crude protein, phosphorus and total alkaloids were found during July. It is, therefore, concluded that the maximum production of different metabolites were found to be in the month of July and it is the suitable month for harvesting tubers.